2+x(x-3)=20

Simple and best practice solution for 2+x(x-3)=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+x(x-3)=20 equation:


Simplifying
2 + x(x + -3) = 20

Reorder the terms:
2 + x(-3 + x) = 20
2 + (-3 * x + x * x) = 20
2 + (-3x + x2) = 20

Solving
2 + -3x + x2 = 20

Solving for variable 'x'.

Reorder the terms:
2 + -20 + -3x + x2 = 20 + -20

Combine like terms: 2 + -20 = -18
-18 + -3x + x2 = 20 + -20

Combine like terms: 20 + -20 = 0
-18 + -3x + x2 = 0

Factor a trinomial.
(-3 + -1x)(6 + -1x) = 0

Subproblem 1

Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3

Subproblem 2

Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6

Solution

x = {-3, 6}

See similar equations:

| 2x^2+5x-12=-5 | | 1x-10=-6x-10 | | (5m-6)(3m+1)=0 | | -10n-(8+8n)=-6(n-4) | | -35=4n-7 | | 16-3*4=52 | | a-13=-3a-1 | | (5m-1)(3m+6)=0 | | 3/8+b*5/8=-1 | | 2/3+x+6=3/4 | | h=-4.9t^2+15t+10 | | Y-1=-8 | | 15m^3+13m^2-6m=0 | | 32+4c(c-1)=(4c+5) | | x^3-3x+7=0 | | 6+x/(-8)=4/7 | | 16x^2-5x+9=-29x | | 3z^2-4z=-7 | | 7=6x-10 | | -9(2b+3)+(19b-5)=0 | | 8x+2=5x+17 | | 1.3(8-x)+3.7x=-5.2 | | -2(x+3)+3x=11 | | 6z^2+43z+7*7z^2+4z-6= | | 27=2m+7-m+3-2m-1 | | 6b-0.4=7b | | -18y+9y= | | 10-8x=90-36x | | (5v+6)(4-v)=0 | | .25x+.1x=9.8 | | 3[(1)]=x | | 2p+22p^2-p= |

Equations solver categories